2017
DOI: 10.1590/0103-6440201601047
|View full text |Cite
|
Sign up to set email alerts
|

Are Maternal Factors Predictors for Early Childhood Caries? Results from a Cohort in Southern Brazil

Abstract: This study aimed to determine the influence of maternal factors on the early development of dental caries in Brazilian preschoolers. This cross-sectional study was nested in a cohort of adolescent mothers. The current wave was performed when the children were aged 24 to 42 months. The questionnaire-based survey targeted adolescent mothers and included demographic and socioeconomic variables as well as the maternal education level. In addition, clinical examinations were performed on the mothers and their child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 16 publications
6
25
0
5
Order By: Relevance
“…Interestingly, the results of present analyses confirm, for the first time, that there is indeed a causal relationship between ECC and psychomotor deficiency in growing children aged 3-6 years old, based on the recruited preschoolers that were measured twice and analyzed over time in the study. It is worth noting that maternal education and occupation, but not paternal metrics, were significantly associated with the gross motor and personal-social CCDI aspects (Table 2), a finding consistent with most of the reported results, emphasizing the critical maternal influence under the content-gradients of SES on ECC for oral health conditions evaluated [17,18,23,24].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Interestingly, the results of present analyses confirm, for the first time, that there is indeed a causal relationship between ECC and psychomotor deficiency in growing children aged 3-6 years old, based on the recruited preschoolers that were measured twice and analyzed over time in the study. It is worth noting that maternal education and occupation, but not paternal metrics, were significantly associated with the gross motor and personal-social CCDI aspects (Table 2), a finding consistent with most of the reported results, emphasizing the critical maternal influence under the content-gradients of SES on ECC for oral health conditions evaluated [17,18,23,24].…”
Section: Discussionsupporting
confidence: 86%
“…Modern research on caries has indicated that the non-dental risks of ECC may include a low level of SES, other vulnerable sub-populations with disparities, and/or certain minority ethnical vs. racial groups, etc. [13][14][15][16][17][18][19][20][21][22][23][24][25]. Therefore, there is an urgent need to identify the critical risks of ECC and also target the high-risk sub-populations on prevention and effective protocols for subsequent proper treatments vs. managements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Similar research investigation conducted by Pinto et al suggested that dmfs score of children between the age of 2 years to 3. 5 years -------------------------------------------------------------------------------Received on 17-02-2021 Accepted on 27-06-2021 was linked with the prevalence of caries among mothers but gingival bleeding in mothers was not linked with dmfs score of child 8 . Prevalence of dental caries in children between the age of 11-12 years was positively associated to the maternal caries experience 9 , even if, in past year, the mothers have any active decay 10 .…”
Section: Introductionmentioning
confidence: 93%